(untitled) (GEON Journal (Management, Organizations and Business), 2017)
One of the main objectives of this document is to obtain more knowledge about the different impacts and to support decision making in social policy, especially in the evaluation and allocation of resources to social investment programs or units, where it appears necessary Have concepts and tools that allow the measurement of social value in its different dimensions. When planning a program it is essential to determine and take into account the effects that it can have on the population. The depth and breadth of the evaluation of Social Value and the activities designed to adapt the program to social criteria depend on the predictable burden, the sensitivity of the services to be offered, the complexity of the program, the information And the evaluation phase in progress. Particular attention should be given to those programs that typically have large social impacts. In order to define the framework and possible central aspects of the assessment of social value, it will be necessary to classify and examine the social effects of the planned program according to its impact, size and importance, using commonly available information and relevant work material . Based on this information, the corresponding terms of reference for the assessment of social value will be formulated. This document is mainly aimed at technicians and specialists in social activity in institutions that need to evaluate social programs.